Poster presentation Ecotoxicological modelling within a sewage distribution system for a cost-efficient prioritization of upgrading treatment processes - Vasquez Christodoulou, Marlen (My University, 2026)
Modestou C, Daskalakis E, Vasquez MI, Ecotoxicological modelling within a sewage distribution system for a cost-efficient prioritization of upgrading treatment processes, poster presentation, 10th Micropol & Ecohazard Conference of the International Water Association, Vienna, Austria, 17-20 September 2017.